The Effect of Transformational Leadership of School Principals and the Role of Management Information Systems on Organizational Commitment and Its Implications for the Development of Teacher Professionalism at SMPN Dayun District - Faizah, Iis; Sri Budi Herawati, Endang (Journal of Educational Sciences, 2025)
This study analyzes the influence of transformational leadership, Management Information Systems (MIS), and organizational commitment on the professional development of teachers at SMPN Dayun Subdistrict. The research uses a quantitative correlational approach, involving all teachers through a saturated sampling technique. Data were collected using questionnaires and analyzed through path analysis with SmartPLS. The findings show that transformational leadership has a significant positive effect on teacher professional development (β = 0.464; T = 4.962; p = 0.000). MIS also demonstrates a significant positive effect (β = 0.384; T = 3.151; p = 0.000), as does organizational commitment (β = 0.498; T = 6.187; p = 0.000). Organizational commitment acts as a strong predictor mediating the influence of transformational leadership (β = 0.788) and MIS (β = 0.808) on professional development. The structural model indicates that transformational leadership and MIS jointly explain 56.5% of the variation in teacher professionalism (R² = 0.565), confirming their dominant role in enhancing teacher professional competence.